Utilizing the Platform Merdeka Mengajar in Elementary Schools: A Fundamental Effort for Learning Reform in Indonesia - Hasman, Nurul Muhlishah; Krismanto, Wawan; Hasan, Kamaruddin; Zainal, Zaid (The Indonesian Institute of Science and Technology Research, 2025)
Technology for teachers has a strategic role in supporting the learning reform, and in Indonesia, this process is currently taking place through the PMM. Therefore, this research aims to describe aspects of PMM implementation in elementary schools and the learning reform after teachers utilize PMM? Qualitative descriptive methods were used in this study. The participants were 6 principals and 11 teachers from 6 elementary schools in Cluster XVI Region 3 Parepare City, South Sulawesi, Indonesia. Data were collected using interviews, observation, and documentation techniques. The research data were analyzed in three stages: data condensation, data display, and conclusions. The results showed that aspects of PMM implementation are school support, external support, teachers' learning collaboration, benefits, and barriers. The characteristics of learning after PMM implementation are the diversity of learning methods, utilization of technology in learning, application of differentiated learning strategies, application of project-based learning, diversity of learning media, and increased student engagement. Various changes in learning characteristics after using PMM indicate significant reforms in the quality of the learning process.